Driving forces for implementation of public private partnerships (PPP) in Malaysia and a comparison with the United Kingdom - Ismail, Suhaiza (Emerald Insight, 2014)
Purpose - The objectives of this present study are twofold. First, it aims to investigate the factors forcing the implementation of PPP in Malaysia. Second, the study intends to compare the driving forces for PPP implementation in Malaysia to the United Kingdom. Design/methodology/approach - Using a questionnaire survey, 122 responses were received from respondents in Malaysia and the responses were analysed using descriptive analysis, which included the mean and mean score ranking. In comparing to the driving factors in the United Kingdom, evidence from prior studies that adopted a similar questionnaire instrument was obtained and analysed. Findings - The results show that the top three driving forces for PPP implementation in Malaysia are ‘economic development pressure of demanding more facilities’, ‘private incentive’ and ‘shortage of government funding’. Although comparison of the results between the two countries found that both countries regarded all the factors, to some extent, as important, different countries have a different priority for each of the driving forces. The findings imply that the unique nature of PPP in different countries is reflected in the different motivation factors of each country to implement PPP. Originality/value – The present study not only offers insights on the key driving forces for PPP implementation in Malaysia but also useful information on the comparison of motivation factors to the pioneer of PPP implementation (i.e., the United Kingdom).